Воля та волевиявлення як умови дійсності правочину - Бахаєва, А. С.; Bakhaieva, A. S.; ORCID: http://orcid.org/0000-0002-6498-2213 (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 2 (77). - С. 183-186, 2017)
Досліджено дискусійні питання щодо визначення юридичної природи волі та волевиявлення як умови дійсності правочину та їх місця в системі юридичних фактів. Проаналізовано кілька основних підходів до визначення правової природи волі та волевиявлення. На підставі результатів наукових здобутків та доктринальних положень, здійснених у сфері правочинів, зроблено спробу з’ясувати місце волі та волевиявлення серед юридичних фактів і їх правову природу. Зроблено висновок, що правочин, вчинений із порушенням волі та волевиявлення, як юридичний факт належить до неправомірних дій, а отже, – до правопорушень. Проте, незважаючи на недійсність правочину з точки зору об’єктивного права, за певних умов такі правочини можуть визнаватися судом дійсними, оскільки не порушують конкретних суб’єктивних прав інших осіб.

Despite the fact that the work on improving and upgrading civil law is going on, the issues related to the problems of recognition of transactions as invalid are not fully covered. Although there is a huge range of research in modern science that has accumulated around the block of invalid transactions, there is no single opinion within civil law doctrine concerning the legal nature of the will and expression of will as a condition for the transaction’s validity and their place in the system of legal facts. Analyzing the literature on this issue, there are several basic approaches to determining the will and expression of will as a condition for the transaction’s validity and their place in the system of legal facts. The opinions of scholars on this subject were divided, as the result, we can divide the positions of the authors into three groups. The first argue that since the transaction – is the action, then its consequences are associated with the expression of will. The second position is based on the link that the expression of will is impossible and, most important, is generated by the will, therefore, the main thing in the transaction – is the internal will of a person. The third position, and the author agrees with it, evaluates the will and expression of will only in their combination. The author has conducted the analysis of the transaction and the invalid transaction in the light of the will and expression of will for the domestic legal theory and classification of legal facts that allows assigning them to the group of lawful or unlawful actions. It has been concluded that the transaction committed with the violation of the will and expression of will as a legal fact belongs to unlawful actions, and therefore – to the offenses. However, despite the invalidity of the transaction in terms of the objective law, such transactions, under certain conditions, may be recognized as valid by the court, because they do not violate specific subjective rights of others.

Исследованы дискуссионные вопросы об определении юридической природы воли и волеизъявления как условия действительности сделки и их места в системе юридических фактов. Проанализировано несколько основных подходов к определению правовой природы воли и волеизъявления. На основании результатов научных достижений и доктринальных положений, совершённых в сфере сделок, сделана попытка выяснить место воли и волеизъявления среди юридических фактов и их правовую природу. Сделан вывод, что сделка, совершённая с нарушением воли и волеизъявления, как юридический факт относится к неправомерным действиям, а следовательно, – к правонарушениям. Однако, несмотря на недействительность сделки с точки зрения объективного права, при определённых условиях такие сделки могут признаваться судом действительными, поскольку не нарушают конкретных субъективных прав других лиц.
Воля и волеизъявление как условия действительности сделки
Will and expression of will as conditions for the transaction’s validity
Бахаєва А. С. Воля та волевиявлення як умови дійсності правочину / А. С. Бахаєва // Вісник Харківського національного університету внутрішніх справ. - 2017. - Вип. 2. - С. 183-189.
Бахаєва А. С. "Воля та волевиявлення як умови дійсності правочину." Вісник Харківського національного університету внутрішніх справ 2 (2017): 183-189.
Bakhaieva, A.S. (2017), “Will and expression of will as conditions for the transaction’s validity” [Volia ta volevyiavlennia yak umovy diisnosti pravochynu], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 183–189.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; воля; волевиявлення; правочин; недійсний правочин; правова природа; юридичний факт; will; expression of will; transaction; invalid transaction; legal nature; legal facts; свобода; волеизъявления; сделка; недействительная сделка; правовая природа; юридический факт